“Where the Turbot Is King”: Murat's “Le Turbot” as Modern Fairy-centric Response to d'Aulnoy's “Le Dauphin” - Melissa A. Hofmann (Wayne State University Press, 2021)
Comparing d’Aulnoy’s “Le Dauphin” and Murat’s “Le Turbot” relation to Straparola’s “Pietro the Fool” and to each other reveals the ways in which the conteuses’ rewriting of the tale allows for differing degrees of women’s control over (their) sexuality. D’Aulnoy and Murat both employ the trope of metamorphosis beyond their source tale’s transformation of the fool and add to the characters and plot in order to explore the issues of sexual consent, female desire and agency, and fidelity. I propose that Murat’s “Le Turbot” purposely engages “Le Dauphin” and fulfills the fairy/women writer ethos of Murat’s “Aux Fées Modernes.”